Jackalope - Stevens, Janet; Crummel, Susan Stevens (San Diego : Harcourt, 2003)
A jackrabbit who wishes to be feared asks his fairy godrabbit for horns and becomes the first jackalope, but there's one condition: he must not tell lies.
Keywords: Jackrabbits -- Fiction; Magic -- Fiction; Honesty -- Fiction; Self-acceptance -- Fiction; Desert animals -- Fiction; Fiction